Valuing Women as Counsel in International Adjudication. (2017) - Parlett, Kate
Abstract : At the outset, it is helpful to draw a distinction between interstate disputes—those at the ICJ and that are administered by some other institutions—and other forms of international arbitration. The reality is that there are relatively few interstate cases. At the moment, there are perhaps a dozen active cases on the docket of the ICJ. That is a relatively full docket for the ICJ, although it has been at that level for a few years now. The Permanent Court of Arbitration (PCA) in its 2015 Annual Report stated that it was administering eight interstate cases. So a good guess of the maximum number of interstate cases that are currently active is perhaps twenty-five.